Increased risk of cancer in patients with fumarate hydratase germline mutation - Lehtonen, H J (BMJ Group, 2006)
Hereditary leiomyomatosis and renal cell cancer (HLRCC) is a tumour predisposition syndrome caused by heterozygous germline mutations in the fumarate hydratase (FH) gene. The condition is characterised by predisposition to benign leiomyomas of the skin and the uterus, renal cell carcinoma (RCC), and uterine leiomyosarcoma (ULMS). To comprehensively examine the cancer risk and tumour spectrum in Finnish FH mutation positive families, genealogical and cancer data were obtained from 868 individuals. The cohort analysis of the standardised incidence ratios (SIR) was analysed from 256 individuals. FH mutation status was analysed from all available individuals (n = 98). To study tumour spectrum in FH mutation carriers, loss of the wild type allele was analysed from all available tumours (n = 22). The SIR was 6.5 for RCC and 71 for ULMS. The overall cancer risk was statistically significantly increased in the age group of 15–29 years, consistent with features of cancer predisposition families in general. FH germline mutation was found in 55% of studied individuals. Most RCC and ULMS tumours displayed biallelic inactivation of FH, as did breast and bladder cancers. In addition, several benign tumours including atypical uterine leiomyomas, kidney cysts, and adrenal gland adenomas were observed. The present study confirms with calculated risk ratios the association of early onset RCC and ULMS with FH germline mutations in Finns. Some evidence for association of breast and bladder carcinoma with HLRCC was obtained. The data enlighten the organ specific malignant potential of HLRCC.